Therapeutic Approach on Oral Mucositis - Kowshihan P1 , Anitha Roy2 , Jayalakshmi Somasundaram3 , Lakshmi.T4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Oral mucositis is a erythematous ulcerated lesion that causes soreness and tissue damage. The lesion leadsto severe pain. It occurs on the comparative of nutrition diet, poor oral hygiene and local and systemicinfections. The pathophysiology of the oral mucositis consists of five phases where initiation phase leads toinjury to the cell. Which leads to activation of transcripts factors which leads to upregulation of inflammatorycytokines and tissue damage as results in subsequent bacterial colonization and cytokines mediated damages. The final phase involves healing through signalling and epithelium proliferation. Maintaining good oralhygiene reduces the severity of the effect and decreases bacteremia . It can be diagnosed by LLLT lowlevel laser therapy. Also can be treated by growth factors, locally applicable gels immune modulators andhematopoietic agents Based on the development of clinical and scientific knowledge standard treatmentplan and further research and analysis is needed for management of mucositis. The severity of oral mucositisalso may be controlled by advanced plant based or nano based phytochemicals.